PRODUKSI RAGI KOPI KULTUR TUNGGAL: Leuconostoc mesenteroides DAN L. paramesenteroides DARI ISOLAT BAKTERI ASAM LAKTAT (BAL) KOPI LUWAK - Mukhammad Fauzi; . Setiadji; . Megawati (JURNAL AGROTEKNOLOGI, 2012)
The presence of microbes mainly lactic acid bacteria are thought to play a role in the process of microbial fermentation in the digestive tract of animals during the mongoose. Efforts need to be engineered so that the yeast fermentation of animal dung to produce a Luwak Coffee Luwak coffee berspesifikasi high quality based on the alleged role of lactic acid bacteria (LAB) in fermented Luwak coffee. This research aims to produce dry yeast single culture of Leuconostoc mesentoroides and Leuconostoc paramesentoroides with the addition of the appropriate filler agent, and to know the level of viability of yeast products produced during storage.The parameters observed in this study include: calculation of bacteria using PCA (Plate Count To), water content of yeast, sugar reduction method of Nelson-Somogy, pH and total acid. Results The study found that the optimum filler agent for the growth of Leuconostoc mesenteroides and Leuconostoc paramesenteroides is rice flour. Microbial population in rice flour filler agent that is still very much during the storage in the second appeal filler agents, namely maize and tapioca. Successive growth of Leuconostoc mesenteroides using cornstarch, tapioaka and rice at the end of the storage is 1.5 x 109 CFU/g, 1.7 x 107 CFU/g and 2.2 x 1010 CFU/g. Paramesenteroides Leuconostoc populations in a row on cornstarch, tapioca and rice is 6.3 x 1010 CFU/g, 2 x 107 CFU/g and 8.6 x 1010 CFU/g.Keywords: dry yeast, lactic acid bacteria, fermentation ,filler agent